Corrosion protection performance of nanocomposite coatings under static, UV, and dynamic conditions - Basiru, Y.A.; Ammar, Sh.; Ramesh, Kasi; Vengadaesvaran, B.; Ramesh, Subramaniam; Arof, Abdul Kariem (Springer Verlag, 2018)
Silicone-modified epoxy polymeric matrix was successfully fabricated and reinforced with 1–2 wt% SiO2, TiO2, and TiSiO4 nanoparticles. Fourier-transform infrared spectroscopy, contact angle measurements, differential scanning calorimetry, and field-emission scanning electron microscopy together with energy-dispersive X-ray spectroscopy were employed to investigate different characteristics of the prepared coatings. To simulate operating conditions, all samples were characterized via electrochemical impedance spectroscopy (EIS) after being subjected to different conditions. Corrosion under static conditions, in which the samples were exposed to a static electrolyte without further change in other parameters, was investigated. Furthermore, to study the effects of ultraviolet (UV) radiation in accelerating the degradation of the coatings, samples were characterized after being subjected to UV while immersed statically in the electrolyte. Additionally, the corrosion protection performance was investigated after subjecting the coated substrates to dynamic conditions involving continuous movement of the sample in the electrolyte, simulating continuous wear of the coated surfaces. Compared with the static condition, the EIS results revealed the vital role of the silicone resin and nanoparticles in improving the stability of the coating film against corrosion degradation in the presence of UV radiation, while poor performance in dynamic condition was recorded for all the coating systems.